2019
DOI: 10.1016/j.pmrj.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Female Office Workers With Moderate Neck Pain Have Increased Anterior Positioning of the Cervical Spine and Stiffness of Upper Trapezius Myofascial Tissue in Sitting Posture

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 49 publications
0
33
0
3
Order By: Relevance
“…Neck pain (NP) is the fourth largest contributor to global disability worldwide [ 14 ]. Individuals with NP show limited range of motion (ROM) [ 15 ], pain adaptive motor control disturbances, such as increased activation of surface musculature [ 15 , 16 ], and modifications in muscle mechanical properties (MMPs) [ 16 , 17 ]. However, these disturbances are not completely understood [ 18 ] and most of these conditions are diagnosed and classified as unspecific [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain (NP) is the fourth largest contributor to global disability worldwide [ 14 ]. Individuals with NP show limited range of motion (ROM) [ 15 ], pain adaptive motor control disturbances, such as increased activation of surface musculature [ 15 , 16 ], and modifications in muscle mechanical properties (MMPs) [ 16 , 17 ]. However, these disturbances are not completely understood [ 18 ] and most of these conditions are diagnosed and classified as unspecific [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that placing the computer screen not in line with the eyes can be related to the appearance of neck pain or musculoskeletal discomfort [28,29]. From a functional perspective, Kocur et al noted that clerks with pain in the cervical spine had advanced the position of the head in a sitting position and presented a higher rigidity in the upper trapezius, although there was no change in the pain threshold when pressing this muscles group [30]. In a more recent study, Kokur et al assessed the relationship between advanced head posture, biomechanical parameters, and the pain threshold related to the pressure in superficial neck musculature in asymptomatic sedentary workers.…”
Section: Discussionmentioning
confidence: 99%
“…In western countries, office workers in particular have been found vulnerable to develop neck pain [ 2 ]. Neck pain symptomatic female office workers showed a protraction of the head relative to the thorax, also known as a protracted “forward head posture” (FHP), compared to asymptomatic controls [ 3 ]. A FHP has frequently been reported for multiple activities and postures, such as driving, computer work, or reading [ 4 ].…”
Section: Introductionmentioning
confidence: 99%